2019
DOI: 10.3390/toxins11050261
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of [CO2] and Temperature on Plant Chemistry of Transgenic Bt Rice and Population Dynamics of a Non-Target Planthopper, Nilaparvata lugens (Stål) under Different Levels of Soil Nitrogen

Abstract: Gaining a better understanding of the interactive effect of projected atmospheric CO2 level increase and the Earth’s rising temperature on plant chemistry (nutritional and defensive characteristics) of transgenic crops is essential when attempting to forecast the responses of target and non-target insects to climate change. In this study, effects of carbon dioxide (CO2; elevated versus ambient), temperature (T; high versus low), and their interactions on leaf nitrogen content (N%) and C:N ratio of transgenic B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Plant nitrogen uptake, nitrogen-level status, and C: N ratio could affect the production of exogenous Bt toxins for Bt crops (Gao et al, 2009;Jiang et al, 2013). Numerous studies have shown that eCO 2 can significantly reduce the exogenous Bt protein content of Bt cotton and Bt rice, while increasing their yield (Coviella et al, 2000(Coviella et al, , 2002Chen et al, 2005b;Wu et al, 2011a,b), and also found the "dilution effect" on exogenous Bt protein or inhibition on Bt-transgene expression (Chen F. J. et al, 2011;Jiang et al, 2017;Liu et al, 2019). Moreover, elevated CO 2 also affected the production of primary and secondary metabolites, and the defense mechanisms of crop plants (e.g., JA and SA) (Stiling and Cornelissen, 2007;Sun et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Plant nitrogen uptake, nitrogen-level status, and C: N ratio could affect the production of exogenous Bt toxins for Bt crops (Gao et al, 2009;Jiang et al, 2013). Numerous studies have shown that eCO 2 can significantly reduce the exogenous Bt protein content of Bt cotton and Bt rice, while increasing their yield (Coviella et al, 2000(Coviella et al, , 2002Chen et al, 2005b;Wu et al, 2011a,b), and also found the "dilution effect" on exogenous Bt protein or inhibition on Bt-transgene expression (Chen F. J. et al, 2011;Jiang et al, 2017;Liu et al, 2019). Moreover, elevated CO 2 also affected the production of primary and secondary metabolites, and the defense mechanisms of crop plants (e.g., JA and SA) (Stiling and Cornelissen, 2007;Sun et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the results showed that e CO 2 significantly increased maize ear weight per plant and grain weight per ear, while it did not significantly affect the 100-grain weight. It is mainly because e CO 2 can enhance photosynthesis and in turn, has a positive effect on crop biomass and production (Guo et al, 2016 ; Liu et al, 2019 ). Although the maize yield was improved, the comprehensive nutritional quality of maize grain (100-grain weight) could not be improved; it may be due to the decreased nitrogen content at high CO 2 levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon can be explained by the fact that AMF inoculation promoted the absorption and utilization of soil nutrients in maize plants, thus improving the nutrient level (e.g., nitrogen, phosphorus and potassium) of plant leaves Hodge, Helgason & Fitter, 2010; Rodriguez & Sanders, 2015). Many studies have shown that the nitrogen metabolism and nitrogen level of transgenic Bt crops could affect the expression of Bt toxin protein (Wang et al, 2012; Liu et al, 2019). Stimulating in plant N uptake can increase biomass N relative to C and enhance the nitrogen metabolism enzyme (e.g., nitrate reductase, nitrite reductase, and so forth) activity, transgene expression and Bt toxin production of Bt crops (Stitt & Krapp, 1999; Gao et al, 2009; Jiang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%